THE POSSIBILITIES OF TRANSPORT OF CONTAINERS BETWEEN THE FAR EAST AND SLOVAKIA (Perner's Contacts, 2016)
The goal of this article is the comparison of the variants of container transport between the Asian port Singapore and four selected European sea ports (Rotterdam, Hamburg, Koper and Constanta). We chose the method CPM for the analysis of selected variants; then we compared them according to the selected criteria such as transport time and shipping rate.
Keywords: maritime transport; rail transport; transport route